Direct measurements of relaxation times of phosphorus metabolites in the human myocardium - Schindler, R; Krahe, T; Neubauer, S; Hillenbrand, H; Entzeroth, C; Horn, M; Lackner, K; Ertl, G (1992)
The T1 relaxation times of the phosphorus metabolites in human heart muscle measurable by 31P-MR spectra were determined in 12 individuals using a 1.5 Tesla system. Several spectra were recorded consecutively with a pulse repetition time of 1.6 s to 24 s. The T1 times of creatine phosphate (CP), of γ-, α-, β-adenosintriphosphate (ATP), 2,3-diphosphoglycerate (2,3-DPG) together with anorganic phosphate) and phosphodiester (PDE) showed mean measurements of 6.1 ± 0.5, 5.4 ± 0.5, 5.0 ± 0.5, 5.8 ± 1.0, 7.6 ± 1.0, and 5.0 ± 1.0 s (M ± SE). The accuracy of the ISIS technique was tested with a special phantom. T1 times were also measured in standard solutions (20mM CP, 10mM ATP); CP was 8.7 ± 0.2 s and γ-ATP was 9.9 ± 0.7 s. Corrections for partially saturated 31P-MR spectra - at least for CP/ATP ratios - are relatively small.